Assessment on avian diversity, abundance, and species richness for ecotourism promotion in Balugo watershed. - Go, Zainah Belle A.; Casas, Eulito Jr. V. (Tacloban City Zainah Belle A. Go, 2019)
The Balugo watershed in Barangay 104, Salvacion, Tacloban City is an emerging tourist destination. The presence of its falls and the natural features enhanced by its dense forest vegetation provides the unique nature experience for ecotourists. It caters better income generating opportunities- such as bird watching, hiking/mountain climbing and development of eco-park facilities. Assessment on the diversity, abundance, and species richness may be used as a database for local planning, e.g. promotion of eco-tourism, and bio-diversity conservation of avian community in the study area. The objective of this survey is to determine the bird species' diversity, abundance, and species richness of Balugo watershed. Bird observation employed the transect line method once a month, from February 2019 to May 2019. It started before sunrise, which lasted for only 3 to 4 hours, and survey along each established transect lasted for no more than 60 minutes. Identification was aided by a bird expert. The survey confirmed the presence of 36 species of 23 families. The most abundant species was Collocalia troglodytes (Pygmy swiftlet) at the montane forest. The H' index of the entire bird community was high with 3.32. Thus, bird watching as a component of this proposed site for ecotourism development will be viable due to its proximity and high avifaunal diversity.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.